Application of Fe-doped BiOI material in ion exchange extraction of iodide ions

By constructing a photo-electric dual-active membrane electrode using Fe-doped BiOI material, the problems of high energy consumption and severe pollution in iodide ion extraction in existing technologies have been solved. This method achieves efficient, low-energy, and pollution-free iodide ion extraction, improves adsorption capacity and photo-assisted efficiency, and is suitable for the extraction of iodide ions from salt lake brine.

CN119306292AActive Publication Date: 2025-01-14SHANXI JINXINTENG ENVIRONMENTAL PROTECTION TECH CO LTD

Patent Information

Application Number
CN202411460385.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-14
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

Existing technologies for extracting iodide ions from salt lake brine suffer from high energy consumption, severe pollution, and poor selectivity. The traditional ESIX technology, which combines ion exchange and electrochemical methods, consumes even more energy, and BiOI materials perform poorly under an applied light field.

Method used

Fe-doped BiOI material was successfully doped into the BiOI structure through a two-step grinding method to construct a photo-electric dual-active membrane electrode, which was applied to a photo-assisted electro-controlled ion exchange system. The strong electron-donating ability of Fe and the good separation effect of photogenerated electrons and holes improved the adsorption capacity of iodide ions.

Benefits of technology

It achieves efficient, low-energy, and pollution-free iodine ion extraction, with improved adsorption capacity, enhanced photo-assisted efficiency, good material stability and selectivity, and is suitable for complex ionic solution systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306292A_ABST
    Figure CN119306292A_ABST
Patent Text Reader

Abstract

The invention provides application of a Fe-doped BiOI material in ion exchange extraction of iodide ions, and relates to the technical field of iodide ion extraction. According to the preparation method, Fe is successfully doped into a BiOI structure through a two-step grinding method, and the Fe-doped BiOI material is obtained. According to the preparation method disclosed by the invention, more effective separation of photo-induced electrons and holes can be realized, and the photoelectrochemical performance of the Fe-doped BiOI material is improved. The prepared Fe-doped BiOI material is used as a working electrode and is used for extracting iodide ions in a light-assisted electric control ion exchange technology. The Fe-doped BiOI material prepared by the invention is applied to light-assisted electric control ion exchange iodine extraction, and has the characteristics of environmental friendliness and no secondary pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ion exchange, and in particular to application of a Fe-doped BiOI material in extracting iodine ions by ion exchange. Background Art

[0002] Iodine resources are scarce resources, and they are mainly distributed abroad. my country's iodine resources are limited by foreign countries, so it is imperative to extract iodine ions from the existing natural resources of salt lake brine in China. Traditional methods for separating I- in solutions include solvent extraction, liquid membrane extraction, adsorption, electrochemical method, etc. However, these methods generally have problems such as secondary pollution, poor selectivity, low adsorption capacity, and high energy consumption.

[0003] ESIX technology combines traditional ion exchange with electrochemical methods to achieve selective separation of target ions by adjusting the redox potential applied to the membrane. 3- Various membrane materials such as BiOI are used in the electrically controlled ion exchange system to selectively separate iodine ions from the solution. However, the energy source of the entire system is completely dependent on electrical energy, which has a high energy consumption. Even after BiOI is applied with an external light field, the performance is still not optimistic. Therefore, it is of great significance to develop a new material for ion exchange separation of I-.

[0004] Doping with transition metal ions is very important for the application of photoelectrochemical properties. Various ion-doped materials are used in the field of photocatalysis through various preparation methods such as hydrothermal method and microwave method. Fe is a common transition metal element, often Fe 3+ and Fe 2+ It exists in the form of a chemical combination and has redox properties. The light-assisted electrically controlled ion exchange system is precisely the placement and removal of target ions through the participation of redox reactions.

[0005] Therefore, developing an Fe-doped BiOI material to separate and recover iodide ions from salt lake brine in a more efficient, energy-saving, environmentally friendly and pollution-free manner has important economic benefits. Summary of the invention

[0006] The purpose of the present invention is to develop a Fe-doped BiOI material in a photo-assisted electrically controlled ion exchange extraction solution. - The preparation method of the Fe-doped BiOI material of the present invention is simple to operate, low in price, and applied to a light-assisted electrically controlled ion exchange system, and has the advantages of high iodine extraction efficiency, low energy consumption, and no secondary pollution.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The invention discloses an application of an Fe-doped BiOI material in ion exchange extraction of iodine ions, specifically comprising the following steps: mixing the obtained Fe-doped BiOI material, conductive carbon black and PVDF in a mass ratio of 8:1:1, dropping a proper amount of NMP and stirring for 6 hours to obtain a slurry; coating the obtained slurry on a conductive substrate, placing the slurry in a vacuum oven at 60°C for drying for 12 hours to obtain a photo-electric dual-active membrane electrode; then using the prepared photo-electric dual-active membrane electrode as a working electrode, using FTO conductive glass as a counter electrode and Ag / AgCl as a reference electrode to construct a three-electrode working system; finally using the constructed three-electrode working system to extract iodine ions from salt lake brine.

[0009] Preferably, the method for preparing the Fe-doped BiOI material comprises the following steps:

[0010] The bismuth salt and potassium iodide are mixed in equal moles and then subjected to a first grinding process, and then an iron salt is added and subjected to a second grinding process;

[0011] The ground product was washed with deionized water and anhydrous ethanol and dried in turn.

[0012] More preferably, the bismuth salt is bismuth nitrate; and the iron salt is iron nitrate.

[0013] More preferably, the doping amount of iron in the Fe-doped BiOI material is 0.5 wt.%.

[0014] More preferably, the first grinding process and the second grinding process are both performed for 5 minutes.

[0015] More preferably, the drying temperature is 60° C. and the drying time is 6 hours.

[0016] Compared with the prior art, the beneficial effects of the present invention include:

[0017] 1) The present invention successfully doped Fe into the BiOI structure through a two-step grinding method to obtain an Fe-doped BiOI material. The present invention can achieve more effective separation of photogenerated electrons and holes, and improve the photoelectrochemical performance of the Fe-doped BiOI material.

[0018] 2) Photo-assisted electrically controlled ion exchange extraction of Fe-doped BiOI material developed by the present invention -The possible mechanism is as follows: due to the introduction of Fe element, Fe replaces one of the Bi in the Bi-O-Bi layer to form Fe-O-Bi. Fe has a stronger electron donating ability, resulting in a large number of electrons on the surface of the material absorbing light energy after the external light field is introduced. The number of valence electrons jumping from the valence band to the conduction band becomes larger, and the space positive charge region formed by the holes left by the valence electron jump is stronger, which makes the I- and free electrons in the solution migrate faster and more into the membrane, so that more iodine ions can enter between its layers, thereby improving the overall adsorption capacity.

[0019] 3) The Fe-doped BiOI material prepared in the present invention is applied to light-assisted electrically controlled ion exchange iodine extraction, which is environmentally friendly and has no secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic diagram of a light-assisted electrically controlled ion exchange iodine extraction device;

[0021] Figure 2 XRD spectra of BiOI and Fe-BiOI materials prepared in Example 1;

[0022] Figure 3 This is a SEM image of the Fe-BiOI material prepared in Example 1 of the present invention;

[0023] Figure 4 This is the SEM image of BiOI material;

[0024] Figure 5 This is the EDS spectrum of the Fe-BiOI material prepared in Example 1 of the present invention;

[0025] Figure 6 Cyclic voltammetry curves of the Fe-BiOI material prepared in Example 1 of the present invention under dark and light conditions;

[0026] Figure 7 Cyclic voltammetry curves of BiOI and Fe-BiOI materials prepared in Example 1 under illumination conditions;

[0027] Figure 8 The UV-visible diffuse reflectance spectra of BiOI and Fe-BiOI materials prepared in Example 1;

[0028] Fig. 9 The adsorption capacity diagram (a) and photo-assisted efficiency diagram (b) of Fe-BiOI materials with different doping ratios in ESIX and P-ESIX systems; the separation factor of Fe-BiOI materials under competing anion conditions (c); and the cycle stability (d). DETAILED DESCRIPTION

[0029] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0030] Example 1

[0031] 2 mmol Bi(NO3)3·5H2O and 2 mmol KI were ground together for 5 min. After grinding evenly, Fe(NO3)3·9H2O was added and grinding was continued for 5 min. The mixture was washed by centrifugation with deionized water and anhydrous ethanol for 3 times each and vacuum dried for 12 h to obtain Fe-BiOI material.

[0032] 2 mmol of Bi(NO3)3·5H2O and 2 mmol of KI were co-grinded for 5 min, washed by centrifugation with deionized water and anhydrous ethanol for 3 times respectively, and vacuum dried for 12 h to obtain BiOI material.

[0033] The prepared Fe-BiOI material was mixed with conductive carbon black and PVDF in a mass ratio of 8:1:1, uniformly ground in an agate mortar, and an appropriate amount of NMP was added and stirred in a stirring station for 6 hours to obtain a Fe-BiOI paste slurry, which was uniformly coated on the pretreated FTO conductive glass conductive surface (pretreatment was ultrasonic cleaning with anhydrous ethanol for 1 hour), and dried in a vacuum oven at 60°C for 12 hours to obtain a photo-electric dual-active membrane electrode.

[0034] Example 2

[0035] The BiOI material and Fe-BiOI material prepared in Example 1 were characterized by XRD and SEM. Figure 2-Figure 4 As shown. Figure 2 The diffraction peaks at 9.7°, 19.4°, 24.3°, 29.6°, 31.7°, 37.1°, 39.4°, and 45.4° correspond to the BiOI (JCPDS-10-0445) (001), (002), (101), (102), (110), (103), (004), and (200) crystal planes. This indicates that the BiOI prepared by the grinding method is almost consistent with the standard card, which is a typical tetragonal phase, and BiOI has been successfully prepared. The doping of Fe in Fe-BiOI does not affect the peak shape of the material, and there is no appearance of impurity peaks. The diffraction peak position shifts slightly to the right, which may be due to the Fe 3+ Ionic radius and Bi 3+ The difference in ionic radius supports the conclusion that Fe 3+ Successfully doped into the BiOI lattice.

[0036] Figure 3 and Figure 4Figure 2 is the SEM image of BiOI material and Fe-BiOI material. It can be seen that both BiOI material and Fe-BiOI material have nanosheet structures. The doping of Fe element does not change their morphology. The thickness of Fe-BiOI nanosheets changes due to the doping of Fe element. The doping of metal ions may control the direction of crystal growth, thereby affecting the thickness of the crystal. The active adsorption sites may become more, which is more conducive to the placement and removal of I. Figure 5 This is the total spectrum of the EDS element distribution map of the Fe-BiOI material, showing that the mass fraction of Fe is 0.5%, which is consistent with the prepared Fe-BiOI, indicating that Fe-BiOI has been successfully prepared.

[0037] Example 3

[0038] The photoelectrochemical properties of the material were characterized by cyclic voltammetry and ultraviolet-visible diffuse reflectance characterization. The specific methods are as follows:

[0039] The Fe-doped BiOI material, conductive carbon black and PVDF were uniformly ground in an agate mortar at a mass ratio of 8:1:1, and an appropriate amount of NMP was added and stirred on a stirring station for 6 hours. The obtained paste slurry was evenly coated on the pretreated FTO conductive glass conductive surface (pretreatment was to ultrasonically clean the conductive glass with anhydrous ethanol for 1 hour), and vacuum dried at 60°C for 12 hours to obtain a photo-electric dual-active membrane electrode.

[0040] The above-mentioned photo-electric dual active membrane electrode is used as the working electrode to construct a light-assisted electrically controlled ion exchange iodine extraction device, such as Figure 1 shown.

[0041] Figure 1 (a) is the photo-electric dual active membrane electrode I-pre-desorption chamber, Figure 1 (b) is the adsorption chamber. ① and ⑧ are circulation chambers I and II respectively, ② and ⑨ are photo-electric dual active membrane materials, ③ and ⑩ are counter electrodes, ④ and is the reference electrode, ⑤, For the liquid collection hole, ⑥, It is the upper cover of the device, made of polytetrafluoroethylene,⑦, It is a peristaltic pump. The xenon lamp was used as the light source and the whole experiment was carried out in a dark box.

[0042] The FTO conductive glass is the counter electrode and the reference electrode is the Ag / AgCl electrode.

[0043] The liquid path system in the present invention is a complete path system formed by connecting the peristaltic pump and the circulation device through a rubber tube. The liquid inlet is located at the lower right corner of the right side of the circulation device, facing away from the coated surface of the membrane material, and the liquid outlet is located at the upper left corner of the left side of the device, facing away from the counter electrode. Such water flow direction enables the entire liquid path system to achieve the circulation effect and reduces the damage and impact on the membrane material.

[0044] The present invention Figure 1 The entire device is made of quartz glass, which facilitates the light source to illuminate the entire device. The upper cover of the circulation device is made of polytetrafluoroethylene to reduce the scattering and loss of the light source. The entire experimental device is operated in a dark box.

[0045] In the present invention, the oxidation (reduction) potential is preferably 0.5-0.7V (-0.5V-0.7V), and more preferably 0.6V (-0.6V).

[0046] In the present invention, the time for each elution and adsorption is consistent, which is about 0.5-6h, more preferably 0.5-1h, and more preferably 0.5h.

[0047] In the present invention, the eluent electrolyte is preferably a sodium sulfate solution, and the concentration of the sodium sulfate solution is preferably 0.05 to 0.15 mol / L, more preferably 0.08 to 0.12 mol / L, and more preferably 0.1 mol / L.

[0048] The electrolyte of the adsorption solution in the present invention is preferably a potassium iodide solution, and the concentration of iodine in the potassium iodide solution is preferably 10-80 mg / L, more preferably 30-70 mg / L, and even more preferably 50-60 mg / L.

[0049] Figure 6 These are the CV curves of Fe-BiOI (darkness) and Fe-BiOI (illumination). It can be seen that Fe-BiOI has a pair of obvious redox peaks. After applying the external light field, the electroactive area is significantly increased, indicating that due to the introduction of light, a large number of electrons on the surface of the material absorb energy and turn into photoelectrons that enter the entire system. The increase in the number of free electrons in the system increases the peak current and the electroactive area.

[0050] Figure 7 The CV curves of BiOI (illumination) and Fe-BiOI (illumination) show that Fe-BiOI (illumination) has a larger electroactive area than BiOI (illumination), which is mainly attributed to the Fe 3+ Doping, replacing part of Bi 3+ This allows the material to have more free electrons. Under the stimulation of the light field, more photoelectrons enter the system, thereby increasing the peak current and the electroactive area.

[0051] Figure 8(Left) is the visible light absorption wavelength range of BiOI and Fe-BiOI, which are 671nm and 676nm respectively. The absorption wavelength range undergoes a slight red shift, indicating that the absorption of visible light is enhanced by Fe doping. Figure 8 (right) is through Figure 8 (Left) The band gap values ​​(Eg) of BiOI and Fe-BiOI are obtained by conversion and drawing. BiOI is 1.79eV and Fe-BiOI is 1.76eV. The reduction of the band gap indicates that Fe-BiOI needs less energy to jump from the valence band to the conduction band, making it easier for electrons to absorb energy and turn into photoelectrons, which in turn leads to an increase in the number of electrons in the system and improves the efficiency of the system. Therefore, Fe-BiOI materials have better photoelectrochemical activity.

[0052] Example 4

[0053] Fig. 9 (a) is the adsorption experiment of Fe doped into BiOI at different doping ratios. Fig. 9 (b) is the photo-assisted efficiency of different doping ratios, and it can be concluded that 0.5% is the optimal doping ratio. The introduction of the external light field increases the solution concentration of the pure BiOI reaction system from 3.32ppm to 5.19ppm, and the adsorption capacity increases from 162mg·g -1 Increased to 258mg·g -1 , the photo-assisted efficiency was 59.3%; the concentration of the Fe-BiOI reaction system solution increased from 3.48ppm to 6.57ppm, and the adsorption capacity increased from 172mg·g -1 Increased to 312 mg g -1 The photocatalytic efficiency is 81.3%. The successful doping of Fe increases the photocatalytic efficiency by 22%. The improvement of photocatalytic efficiency is mainly due to the substitution of Bi in Bi-O-Bi by Fe doping to form Bi-O-Fe. After the introduction of visible light, Bi-O-Fe carries more electrons, and the absorbed energy is converted into photogenerated electrons that can enter the electric field. At the same time, the escape of photogenerated electrons and the external drive of the electric field form a space charge region in the material, which synergistically accelerates the solution I - Migration in solution increases I - The adsorption capacity of the photo-assisted electrochemical switch ion exchange technology system has been further improved, thereby further improving the iodine extraction efficiency.

[0054] The ion selectivity of P-EIXM is very important for the iodine extraction process of P-ESIX. - To study the selectivity of F - / I - ,Cl - / I - and Br- / I - The experiments were conducted in a mixed solution system with a molar ratio of 1:1. Fig. 9 (c) shows the selectivity of Fe-BiOI. - / I - ,I - / F - ,I - / Cl - ,I - / Br - The separation factors are 1, 2.18728, 2.10851, and 4.31321, respectively. - , Cl - and Br - with I - It belongs to the halogen element and is similar to I - have the same valence state and similar ionic radius, the main reason may be that I - The migration energy barrier of BiOI is the largest, and the adsorption energy barrier is the smallest, which leads to the - The selectivity of - , due to F - It has the lowest migration energy barrier, the highest adsorption energy barrier, and its selectivity is second only to I - , its Cl - and Br - The migration energy barrier and adsorption energy barrier of Fe-BiOI are average, so the selectivity is average. Analysis shows that the selectivity of BiOI to ions is affected by the combined effect of the migration energy barrier and adsorption energy barrier of ions. - Effective and selective extraction.

[0055] In order to verify the stability of Fe-BiOI, we conducted multiple adsorption experiments (0.6 V). Fig. 9 (d) shows that after 10 cycles of adsorption and desorption, the adsorption rate of the material is still above 87.7%, which indicates that Fe-BiOI has good stability. The main reasons for the decrease in adsorption efficiency may be as follows: desorption is required before each adsorption, and some I- - It did not successfully escape from the specific binding site, resulting in a decrease in its adsorption rate.

[0056] In summary, the study found that Fe-BiOI materials can be used in the ESIX system at 172 mg·g -1 The adsorption capacity of the P-ESIX system was increased to 312 mg g -1, the photocatalytic efficiency is as high as 81.3%. In addition, Fe-BiOI also has good stability and excellent selectivity, and can be recycled and efficiently extract iodine in complex ion solution systems. Unlike traditional ion exchange technology, Fe is doped into the material to replace the Bi in the Bi-O-Bi layer in the unique layered structure of BiOI with Fe-O-Bi. The difference in ion radius and the number of electrons results in better conductivity and excellent electrochemical activity, while also improving the photocatalytic ability of the material, providing more free electrons for the entire reaction system, and improving the overall adsorption capacity and photocatalytic efficiency. Ion doping provides a more novel and efficient method for P-ESIX technology to efficiently and selectively extract target ions.

[0057] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. Application of Fe-doped BiOI material in ion exchange extraction of iodide ions.

2. The use according to claim 1, characterized in that: The preparation method of the Fe-doped BiOI material comprises the following steps: The bismuth salt and potassium iodide are mixed in equal moles and then subjected to a first grinding process, and then an iron salt is added and subjected to a second grinding process; The ground product was washed with deionized water and anhydrous ethanol and dried in turn.

3. The use according to claim 2, characterized in that: The bismuth salt is bismuth nitrate; and the iron salt is iron nitrate.

4. The use according to claim 3, characterized in that: The doping amount of iron in the Fe-doped BiOI material is 0.5 wt.%.

5. The use according to claim 2, characterized in that: The time for the first grinding process and the second grinding process is 5 minutes.

6. The use according to claim 2, characterized in that: The drying temperature is 60° C. and the drying time is 6 hours.

7. The use according to claim 1, characterized in that: The Fe-doped BiOI material is used to extract iodine ions in a light-assisted electrically controlled ion exchange technology.

Citation Information

Patent Citations

  • Preparation and application of bismuth oxychloride as photocatalyst

    CN101879455A

  • BiOI composite material and preparation method and application of BiOI composite material

    CN102631936A

  • Preparation method and application of iodide ion doped modified Fe-MOF block electrode material

    CN114566394A

  • Granulating agent for anion adsorbent, preparation method and anion adsorbent

    CN115254072A

  • I-doped BiOIO3 photocatalyst as well as preparation method and application thereof

    CN116212900A

Cited By

  • Preparation method and application of Bi2O2CO3 modified material

    CN122187205A